The Effect of Fluid Velocity on the Diffusion of Trimethylene Glycol through a Reverse Osmosis Membrane in Microchannel -X - Sugeng Hadi Susilo; Zahratul Jannah; R.N. Akhsanu Takwim (Logic : Jurnal Rancang Bangun dan Teknologi, 2021)
The study aims to observe the diffusion process which is influenced by different velocity and fluid concentrations. Using a microfluidic system and the diffusion process through a reverse osmosis membrane. The research was carried out by flowing fluid into the microchannel. The diffusion process is known by measuring and analyzing the density of liquid waste aquades-trimethylene glycol. The results showed the amount of diffusion through the membrane was influenced by flow velocity and fluid concentration. this is because the velocity of the flow produces pressure on the wall so that it pushes the fluid to diffuse through the membrane.